The clinical-stage drug BTZ-043 accumulates in murine tuberculosis lesions and efficiently acts against Mycobacterium tuberculosis - Andreas Römpp; Axel Treu; Julia Kokesch-Himmelreich; Franziska Marwitz; Julia Dreisbach; Nadine Aboutara; Doris Hillemann; Moritz Garrelts; Paul J. Converse; Sandeep Tyagi; Sina Gerbach; Luzia Gyr; et al. (Nature Communications)
Abstract The development of granulomas with central necrosis harboring Mycobacterium tuberculosis (Mtb) is the hallmark of human tuberculosis (TB). New anti-TB therapies need to effectively penetrate the cellular and necrotic compartments of these lesions and reach sufficient concentrations to eliminate Mtb. BTZ-043 is a novel antibiotic showing good bactericidal activity in humans in a phase IIa trial. Here, we report on lesional BTZ-043 concentrations severalfold above the minimal-inhibitory-concentration and the substantial local efficacy of BTZ-043 in interleukin-13-overexpressing mice, which mimic human TB pathology of granuloma necrosis. High-resolution MALDI imaging further reveals that BTZ-043 diffuses and accumulates in the cellular compartment, and fully penetrates the necrotic center. This is the first study that visualizes an efficient penetration and accumulation of a clinical-stage TB drug in human-like centrally necrotizing granulomas and that also determines its lesional activity. Our results most likely predict a substantial bactericidal effect of BTZ-043 at these hard-to-reach sites in TB patients.